Perlindungan Hukum Terhadap Pemegang Sertipikat Hak Atas Tanah Ganda Yang Dikeluarkan Oleh Kantor Pertanahan Nasional Dalam Objek Yang Sama (Analisis Putusan Mahkamah Agung Nomor 1820 K/Pdt/2017) - Tamami Dirga Jeis; Alpi Sahari; Ahmad Fauzi (Iuris Studia: Jurnal Kajian Hukum, 2021)
The legal consequences for land title certificates with the same object, due to inaccuracy, inaccuracy, and negligence of the head of the land office, the consequence of issuing double certificates is legal uncertainty regarding ownership rights to property or land. ownership, so that the position is weakened and the double certificate can be overturned by the court. Legal protection for holders of land rights certificates, namely rights holders, namely the plaintiffs get legal protection as in Government Regulation Number 24 of 1997, and Article 19 paragraph (2) letter c, Article 23 paragraph (2), Article 32 paragraph (2). and Article 38 paragraph (2) of the UUPA, that documentary proof of rights acts as a strong means of proof. Analysis of the Supreme Court Decision Number 1820 K / Pdt / 2017 which states that the Property Rights Certificate is no longer valid no. 535 Pananjung Village is now Pangandaran Village, which was previously under the name YY changed to the name of Mr TAPT. The specification of this research is descriptive analysis, descriptive analysis means that this research is expected to obtain a detailed and systematic description of the problems to be studied. Due to the legal consequences of multiple land rights certificates with the same object, due to inaccuracy, inaccuracy, and negligence of the head of the land office, the result of the issuance of a double certificate is legal uncertainty regarding ownership of rights over ownership or control of land, so that the status of the certificate becomes weak and a double certificate can be canceled by the court, the next result is the revocation of the certificate. Legal protection for holders of land title certificates, namely rights holders, namely the plaintiffs receive legal protection as in Government Regulation no. 24 of 1997, and Article 19 paragraph (2) letter c, Article 23 paragraph (2), Article 32 paragraph (2) and Article 38 paragraph (2) of the UUPA, that letters of proof of rights act as a strong means of proof. Analysis of the Supreme Court Decision Number 1820 K / Pdt / 2017 which states that canceling the Freehold Certificate no. 535 Pananjung Village, now Pangandaran Village, formerly on behalf of YY, transferred to on behalf of Tuan TAPT, it can be seen that legal certainty and legal protection for land title certificate holders have not been fully realized